Clinical study of cervicogenic headache (2020)
The cervicogenic headache was studied to get a deeper insight into the pathogenetic mechanisms, and clinical presentation forms. Material and Methods. Eleven female patients, ranging from 34 to 81 years-old, with cervicogenic headaches, were studied and correlated with NMR images of the cervical spine. Results. Intense neck pain irradiated to parietal, occipital, temporal regions, and shoulders were correlated with NMR images of the degenerated cervical spine. Also, lumbar spine pathology, osteoporosis, gallstones, and cholecystitis were found. The following associated neurological, neurobehavioral, and metabolic diseases comorbidities were observed, such as blood hypertension, diabetes, obesity, hypothyroidism, partial epilepsy, tremor, familial stress, memory, sleep disorders, and dizziness. Also, we found mixed cervicogenic headaches and migraines in 50% of cases studied. Conclusion. The headache and the associated images of cervical pathology have been clinically interpreted as cardinal signs of cervicogenic headache. A mixed cervicogenic mixed type was observed.